Evening intake of aspirin is associated with a more stable 24-h platelet inhibition compared to morning intake: a study in chronic aspirin users. (18th May 2016) - van Diemen, Jeske Joanna Katarina; Fuijkschot, Wessel Willem; Wessels, Tim Jon; Veen, Gerrit; Smulders, Yvo Michiel; Thijs, Abel
Abstract: Daily generation of novel platelets may compromise aspirin's platelet inhibitory action, especially near the end of the regular 24-h dosing interval. A contributor to this attenuation could be the endogenous circadian rhythm. The primary objective of this study was to assess platelet activity 12 and 24 h after different times of aspirin intake (c.q. 8.00 AM and 8.00 PM). A randomized open-label crossover study was conducted, comprising outpatients with stable cardiovascular disease taking aspirin once daily. We measured platelet aggregation with the platelet function analyzer (PFA)-200 ® and light transmission aggregometry (LTA). The attenuation of aspirin's inhibitory action was most apparent in the 8.00 AM regimen. The platelet function analyzer—closure time was 78 s faster at 24 h than at 12 h after intake in the 8.00 AM regimen (IQR: 166.8–301 vs. 132.8–301; p = 0.006) and 0 s faster at 24 h than at 12 h after intake in the 8.00 PM regimen (IQR: 198.8–837.0 vs. 169.8–301; p = 0.653). The adenosine diphosphate 1.0 µmol/L maximum amplitude was 5.40% higher at 24 h than at 12 h after intake in the 8.00 AM regimen (95% confidence interval (CI): −0.03–−10.8; p = 0.040) and was 0.75% higher 24 h than at 12 h after intake in the 8.00 PM regimen (95% CI: −4.83–3.33; p = 0.705). The platelet inhibitory effect of aspirin decreases after 24 h, particularly after intake in the morning. These results suggest that patients might benefit from evening intake or twice daily intake regimens.